Advertisements
Advertisements
प्रश्न
Without using truth table, show that
(p ∨ q) → r ≡ (p → r) ∧ (q → r)
उत्तर
L.H.S.
≡ (p ∨ q) → r
≡ ~ (p ∨ q) ∨ r ....[p → q → ~ p ∨ q]
≡ (~ p ∧ ~ q) ∨ r ....[De Morgan’s law]
≡ (~ p ∨ r) ∧ (~ q ∨ r) .....[Distributive law]
≡ (p → r) ∧ (q → r) .....[p → q → ~ p ∨ q]
= R.H.S.
APPEARS IN
संबंधित प्रश्न
The negation of p ∧ (q → r) is ______________.
Write the Truth Value of the Negation of the Following Statement :
The Sun sets in the East.
Write the truth value of the negation of the following statement :
cos2 θ + sin2 θ = 1, for all θ ∈ R
Rewrite the following statement without using if ...... then.
If a man is a judge then he is honest.
Rewrite the following statement without using if ...... then.
It 2 is a rational number then `sqrt2` is irrational number.
Without using truth table prove that:
(p ∨ q) ∧ (p ∨ ∼ q) ≡ p
Without using truth table prove that:
(p ∧ q) ∨ (∼ p ∧ q) ∨ (p ∧ ∼ q) ≡ p ∨ q
Without using truth table prove that:
∼ [(p ∨ ∼ q) → (p ∧ ∼ q)] ≡ (p ∨ ∼ q) ∧ (∼ p ∨ q)
Using rules in logic, prove the following:
∼p ∧ q ≡ (p ∨ q) ∧ ∼p
Using the rules in logic, write the negation of the following:
(p → q) ∧ r
Using the rules in logic, write the negation of the following:
(∼p ∧ q) ∨ (p ∧ ∼q)
Without using truth table, show that
p ↔ q ≡ (p ∧ q) ∨ (~p ∧ ~q)
Using the algebra of statement, prove that
[p ∧ (q ∨ r)] ∨ [~ r ∧ ~ q ∧ p] ≡ p
(p → q) ∨ p is logically equivalent to ______
The statement pattern p ∧ (∼p ∧ q) is ______.
(p ∧ ∼q) ∧ (∼p ∧ q) is a ______.
The negation of the Boolean expression (r ∧ ∼s) ∨ s is equivalent to: ______
Without using truth table prove that (p ∧ q) ∨ (∼ p ∧ q) v (p∧ ∼ q) ≡ p ∨ q
If p ∨ q is true, then the truth value of ∼ p ∧ ∼ q is ______.
Which of the following is not a statement?
∼ ((∼ p) ∧ q) is equal to ______.
Without using truth table, prove that:
[p ∧ (q ∨ r)] ∨ [∼r ∧ ∼q ∧ p] ≡ p
Without using truth table, prove that : [(p ∨ q) ∧ ∼p] →q is a tautology.
The simplified form of [(~ p v q) ∧ r] v [(p ∧ ~ q) ∧ r] is ______.
Without using truth table prove that
[(p ∧ q ∧ ∼ p) ∨ (∼ p ∧ q ∧ r) ∨ (p ∧ q ∧ r) ∨ (p ∧ ∼ q ∧ r) ≡ (p ∨ q) ∧ r
The statement p → (q → p) is equivalent to ______.